Sudut Pandang Mahasiswa Pendidikan Bahasa dan Sastra Indonesia Kelas 2022 A Univeritas Riau Terhadap Pembelajaran Arab Melayu (International Forum of Researchers and Lecturers, 2023)
Language has a variety of skills, namely, reading, writing, listening and speaking. In learning Malay Arabic, two language skills are used, namely reading and writing. So, it can be concluded that reading is the process of seeing and understanding something written to obtain information and knowledge and reading is a step in broadening one's horizons. Writing is a productive and expressive activity. Writing activities require a person to be skilled at utilizing what is on his mind, mastering various dictions and understanding language structures. Learning Malay Arabic is essentially a process of learning the rules of the Malay Arabic script which aims to form a generation that is good at writing and reading Malay Arabic script so that it can be preserved for the next generation.